Short range order in Al-Fe-Nb, Al-Fe-Ce and Al-Ni-Ce metallic glasses - Saporiti, María Fabiana Sonia (2010)
Short range order of amorphous samples with Al90Fe7Nb3, Al90Fe5Ce5 and Al90Ni5Ce5 nominal composition (in at.%) was studied by X-ray diffraction (XRD) at room temperature (RT). The total structure factors STot(Q) and the reduced atomic distribution function G(r) were derived from the diffracted intensity IM(Q). All the STot(Q) factors are composed by an initial prepeak followed by a main peak and a second peak with two components. Though the general aspect of the different samples is similar they present slight differences in details that are discussed as a function of the composition and compared with available data in the literature. While in the Al-(Fe, Ni)-Ce alloys two distinct components were observed for the first peak of the G(r) function, a unique broad peak was observed in the Nb containing alloy. The pair correlation function, g(r), for Al90Fe10 at 200 K have been calculated with molecular dynamics simulation (MDS) and it is in good agreement with the experimental results obtained from Al90Fe7Nb3 showing that size effects can be neglected in this sample.